2005
DOI: 10.1200/jco.2005.11.726
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Excess Weight on Cancer Incidences Depending on Cancer Sites and Histologic Findings Among Men: Korea National Health Insurance Corporation Study

Abstract: These findings show that, even in Koreans, obesity clearly increases the risk of many types of cancers and the strength of the associations varies with the organ and histologic type. Because these obesity-related cancers are reported to be rapidly increasing in Korea and many other Asian countries, controlling obesity epidemics could be an effective tool for preventing these cancers in these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
261
3
3

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 359 publications
(292 citation statements)
references
References 34 publications
23
261
3
3
Order By: Relevance
“…We identified 11 eligible cohort studies (Møller et al, 1994;Wolk et al, 2001;Nair et al, 2002;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Batty et al, 2005;Kuriyama et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006), of which 7 on overweight (with a total of 5037 cases) (Calle et al, 2003;Batty et al, 2005;Kuriyama et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006;Samanic et al, 2006) and 10 on obesity (with a total of 6042 cases) (Møller et al, 1994;Wolk et al, 2001;Nair et al, 2002;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Batty et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006) were suitable for metaanalysis. Characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 11 eligible cohort studies (Møller et al, 1994;Wolk et al, 2001;Nair et al, 2002;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Batty et al, 2005;Kuriyama et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006), of which 7 on overweight (with a total of 5037 cases) (Calle et al, 2003;Batty et al, 2005;Kuriyama et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006;Samanic et al, 2006) and 10 on obesity (with a total of 6042 cases) (Møller et al, 1994;Wolk et al, 2001;Nair et al, 2002;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Batty et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006) were suitable for metaanalysis. Characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…With stratification by assessment of obesity, the summary relative risks for the association between obesity and liver cancer were 2.15 (95% CI: 1.66 -2.77) for studies based on measured or self-reported weight and height (Nair et al, 2002;Calle et al, 2003;Batty et al, 2005;Oh et al, 2005;Rapp et al, 2005;N'Kontchou et al, 2006;Samanic et al, 2006) and 1.61 (95% CI: 1.14 -2.27) for studies based on a discharge diagnosis of obesity (Møller et al, 1994;Wolk et al, 2001;Samanic et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The eight cohort studies Wolk et al, 2001;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Engeland et al, 2005;Kuriyama et al, 2005;Oh et al, 2005) and three case -control studies Zatonski et al, 1997;Serra et al, 2002) that were included in the meta-analysis involved a total of 3288 cases. Main characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…We identified eight cohort studies Wolk et al, 2001;Calle et al, 2003;Samanic et al, 2004Samanic et al, , 2006Engeland et al, 2005;Kuriyama et al, 2005;Oh et al, 2005) and four case -control studies (Zatonski et al, 1992(Zatonski et al, , 1997Strom et al, 1995;Serra et al, 2002) that reported results on overweight/obesity and risk of gallbladder cancer. One case -control study (Zatonski et al, 1992) was excluded because this study was included in a multicentre case -control study (Zatonski et al, 1997); the multicentre casecontrol study was included in this meta-analysis.…”
Section: Study Selectionmentioning
confidence: 99%